Cytotoxic, genotoxic and biochemical markers of insecticide toxicity evaluated in human peripheral blood lymphocytes and an HepG2 cell line. (October 2016) - Želježić, Davor; Mladinić, Marin; Žunec, Suzana; Lucić Vrdoljak, Ana; Kašuba, Vilena; Tariba, Blanka; Živković, Tanja; Marjanović, Ana Marija; Pavičić, Ivan; Milić, Mirta; Rozgaj, Ružica; Kopjar, Nevenka
Abstract: This study evaluated the cyto- and genotoxic effects of three pesticides: α-cypermethrin, chlorpyrifos and imidacloprid applied in vitro to human lymphocytes and HepG2 cells for exposure times of 4 and 24 h at concentrations corresponding to OEL, ADI and REL. Assessments were made using oxidative stress biomarkers and the alkaline comet, cytokinesis-block micronucleus cytome and cell viability assays. Low doses of all three pesticides displayed DNA damaging potential, both in lymphocytes and HepG2 cells. At the tested concentrations, all three compounds induced lymphocyte apoptosis, though α-cypermethrin and chlorpyrifos were generally more cyto- and genotoxic than imidacloprid. At the tested concentrations, oxidative stress biomarkers were not significantly altered, and the effects mediated indirectly through free radicals may not have a key role in the formation of DNA damage. It is likely that the DNA damaging effects were caused by direct interactions between the tested compounds and/or their metabolites that destabilized the DNA structure. The tested pesticides had the potential for MN, NB and NPB formation and to disturb cell cycle kinetics in both cell types. There were also indications that exposure to α-cypermethrin led to the formation of crosslinks in DNA, though this would require more detailed study in the future. Graphical abstract: Highlights: Cyto-/genotoxicity of α-cypermethrin, chlorpyrifos and imidacloprid was studied. Human peripheral blood lymphocytes and HepG2 cells were chosen as model cells. Oxidative stress biomarkers, primary and cytogenetic damage were evaluated. Treatments did not induce significant oxidative stress responses. Genome instability in both cell types was induced by direct interactions with DNA.